Microwave‐Assisted Synthesis of Biocompatible Silk Fibroin‐Based Carbon Quantum Dots. (11th December 2017) - Ko, Na Re; Nafiujjaman, Md; Cherukula, Kondareddy; Lee, Sang Ju; Hong, Seoung‐Jin; Lim, Ho‐Nam; Park, Chan Hum; Park, In‐Kyu; Lee, Yong‐Kyu; Kwon, Il Keun
Abstract: A biocompatible silk fibroin‐based carbon quantum dot (SF‐CQD) is first synthesized under microwave irradiation for a short time. This fast and environmentally safe technique produce well‐defined nanosized SF‐CQDs. The SF‐CQDs have good crystallinity, a strong emission peak in the blue‐color region, high quantum yield, and the potential for modification with various functional groups on the surface. These SF‐CQDs demonstrate stable emission, good water dispersity, low toxicity, and good biocompatibility. These properties show the great potential of these SF‐CQDs for use in biomedical applications including bioimaging, biosensing, and drug delivery systems. Abstract : Novel silk fibroin‐based carbon quantum dots (SF‐CQDs) are successfully synthesized via facile microwave‐irradiation method with a reaction time of only 20 min. Nanosized SF‐CQDs with good crystallinity, stable emission in the blue‐color region, high quantum yield, good water dispersity, low toxicity, and good biocompatibility show the great potential of the SF‐CQDs for use in biomedical applications.